2000
DOI: 10.1177/089686080002000511
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Transport Characteristics with Glycerol-Based Dialysate in Peritoneal Dialysis

Abstract: Background Glycerol is a low molecular weight solute (MW 92 D) that can be used as an osmotic agent in continuous ambulatory peritoneal dialysis (CAPD). Due to its low molecular weight, the osmotic gradient disappears rapidly. Despite the higher osmolality at the beginning of a dwell, ultrafiltration has been found to be lower for glycerol compared to glucose (MW 180 D) when equimolar concentrations are used. Previous studies have shown glycerol to be safe for long-term use, but some discrepancies have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Long-term use of glycerol-based dialysate as a dialysis solution showed good results in diabetic patients [ 40,41 ]. Although it is well tolerated, its use is limited because it induces less ultrafiltration per mOsmol than glucose [ 42 ] owing to its greater absorption and lower reflection coefficient [ 43 ]. Another disadvantage is the risk of developing a hyperosmolar syndrome in patients with high absorption rates [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of glycerol-based dialysate as a dialysis solution showed good results in diabetic patients [ 40,41 ]. Although it is well tolerated, its use is limited because it induces less ultrafiltration per mOsmol than glucose [ 42 ] owing to its greater absorption and lower reflection coefficient [ 43 ]. Another disadvantage is the risk of developing a hyperosmolar syndrome in patients with high absorption rates [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crystalloid pressure gradient is the most important driving force. Therefore, these measurements have to be done with a 3.86% glucose solution or another osmotic agent that creates a similar osmotic gradient, for instance glycerol [ 25 ]. When sodium in dialysate and plasma is measured in the beginning of the dwell, for instance after 60 min, the D/P ratio of this electrolyte gives a rough estimation of FWT, because the diffusion of sodium is so low that it can be neglected.…”
Section: Mechanisms Of Fluid Transport and An Assessment In Patientsmentioning
confidence: 99%
“…This in turn may alter the pore size of the peritoneal membrane, resulting in a diminished effective filtration of uremic solutes. Researchers in this field have in fact suggested possible osmotic agent replacements in the form of amino acids, icodextrins, or glycerol 10,24–29 . However, initial results have indicated that there are potential detrimental effects of these alternative molecules, and further investigations are currently in progress to address these problems.…”
Section: Hyperglycemiamentioning
confidence: 99%